慢性阻塞性肺疾病合并原发性支气管肺癌118例临床特征分析 (Zhongguo Fei Ai Za Zhi, 2017)
BACKGROUND AND OBJECTIVE: The aim of this study is to investigate the clinical characteristics of patients with primary bronchopulmonary carcinoma complicated with chronic obstructive pulmonary disease (COPD), and to optimize the early diagnoses in the coexistence of COPD and primary bronchopulmonary carcinoma. METHODS: The clinical data of 118 patients with COPD complicated with primary bronchopulmonary carcinoma were analyzed retrospectively, including age, sex, smoking history, smoking index, clinical symptoms and signs, pathological type, staging, metastasis site and lung function index. 120 patients with simple COPD were selected as control. RESULTS: The smoking rate (55.1%) and smoking index ≥400 branch /year (90.8%) of the patients with COPD complicated with primary bronchopulmonary carcinoma were higher than the simple COPD group (20.8%, 48.0%). The difference between the two groups was statistically significant (P < 0.01). There were no significant differences in the incidence of common symptoms such as cough, sputum, fever, fatigue and dyspnea in COPD complicated with primary bronchopulmonary carcinoma patients with simple COPD group (P > 0.05), while the incidence of hemoptysis, weight loss, chest pain, hoarseness, pleural effusion and atelectasis were significantly higher than those in simple COPD group (P < 0.01). When the patients were first diagnosed as COPD with primary bronchopulmonary carcinoma, 63.6% of the group were advanced or located late, and the distant metastases are common for pleural metastasis and bone metastases. There was no significant difference in forced expiratory volume in one second/forced vital capacity (FEV(1)/FVC), FEV(1)% pre, total lung capacity (TLC) and residual volume (RV)/TLC between the two groups (P > 0.05), but the diffusing capacity of carbon monoxide (DLCO) of COPD patients complicated with primary bronchopulmonary carcinoma was lower than that of simple COPD patients (P < 0.05). In the COPD patients with primary bronchopulmonary carcinoma, squamous cell carcinoma was the most common pathological type (51.7%). Male patients were mainly squamous cell carcinoma (60.7%), while female patients with adenocarcinoma (69.0%). CONCLUSION: COPD combined with primary bronchopulmonary carcinoma occurs in male smokers more. There is higher incidence of squamous cell carcinoma. When they are first diagnosed, most of them are advanced or located late, due to no specific clinical symptoms at the early stages. Periodic chest CT examination for COPD patients can help early diagnoses of primary bronchopulmonary carcinoma.